Drugs, police inefficiencies and gangsterism in violently impoverished communities like Overcome - Taheri-Keramati, Yashar (2013)
This research establishes an understanding of the relationship between gangsterism, the drug commodity and inefficiencies in the state’s policing institution, as well as the consequences of this relationship, in the context of Overcome squatter area in Cape Town. Overcome is representative of other violently impoverished Cape Town communities with its high rate of unemployment, low quality of education, domestic abuse, stagnant housing crisis, lack of access to intellectual and material resources or opportunities for personal growth, gangsterism, inefficient policing, substance-dependency, and violence. This research demonstrates that the current relationship between the gangs, drugs and the police fosters an unpredictable, violent environment, leaving residents in a constant state of vulnerability. The argument is developed around three key historical junctures in the development of organized crime in South Africa, starting with the growth of the mining industry in the Witwatersrand after 1886, followed by forced removals and prohibition like policies in Cape Town circa 1970, and finally the upheaval created around transition away from apartheid in 1994. Research for this paper was both quantitative and qualitative in nature, and included expert interviews on the subjects of police criminality, narcotic sales, and gangsterism. Newspapers articles, crime statistics, books, census figures, and a host of journals were also utilized. Upon reviewing a host of police inefficiencies and criminal collusions, the research concludes that public criminals related to the state, such as police, and private criminals, such as gangsters, work together in a multitude of ways in a bid to acquire wealth, most notably through an illicit drug market today dominated by ‘tik’. It is shown that this violent narcotics market binds police and gangsters together at the expense of creating a state of insecurity for those living in poor drug markets